Missouri Mathematics Project (MMP) Model: Encouraging the Enhancement of Reasoning Ability and the Advanced Mathematical Thinking (AMT) - Elfi Rahmadhani; Septia Wahyuni (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
This article was written aiming to look at the application of the model Missouri Mathematics Project (MMP) in enhancing reasoning ability and the Advanced Mathematical Thinking (AMT) of students. This research is an experimental study with a quantitative approach and Randomized Pretest-Posttest Control Group Design research design. The sample in this study were students of class XI.1 who became an experimental class by giving treatment in the form of learning model Â Missouri Mathematics Project (MMP) and class XI.2 students as a control class by giving treatment using conventional learning. The instruments in this study were tests in the form of pretest and posttest which were used to see the improvement of reasoning ability and the Advanced Mathematical Thinking (AMT) of students. Based on the results of the study it can be concluded that the model Missouri Mathematics Project (MMP) can improve students' reasoning abilities and the Advanced Mathematical Thinking (AMT). For reasoning ability, the average N-gain of the experimental class is 0.76 while the N-gain for the control class is 0.13, while for Advanced Mathematical Thinking (AMT) the average N-gain of the experimental class is 0.66 while the N-gain for the control class is 0.49.